Pengaruh Pertumbuhan Laba, Ukuran Perusahaan dan Konservatisme Akuntansi Terhadap Kualitas Laba - Sari, Silvia; Ayu, Fitria Sari (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of profit growth, company size and accounting conservatism on earnings quality. This study was conducted by analyzing the financial statements of companies in the industrial sector of the goods industry subsector listed on the indonesia stock exchange during the period 2020 to 2024. The sample used in this study were 7 companies in the industrial sector of the goods industry subsector listed on the Indonesia Stock Exchange during the period 2020 to 2024 using a purposive sampling technique. The data used in this study are secondary data in the form of financial statements from each company that has been used as a research sample. Analysis of the research results using the help of eviews student version lite software. The results of the study showed that the best model was the fixed effect model. The results of this study indicate that profit growth, company size and accounting conservatism have a simultaneous effect on earnings quality, and partially profit growth has no effect on earnings quality, company size and accounting conservatism have an effect on earnings quality.